Three-dimensional analysis of the root canal preparation with Reciproc Blue®, WaveOne Gold® and XP EndoShaper®: a new method in vivo - Javier Caviedes-Bucheli; Nestor Rios-Osorio; Diana Usme; Cristian Jimenez; Adriana Pinzon; Jorge Rincón; María M. Azuero-Holguin; Alvaro Zubizarreta-Macho; Jose F. Gomez-Sosa; Hugo R. Munoz (BMC, 2021)
Abstract Background The purpose of this study was to evaluate the changes in canal volume after root canal preparation in vivo with 3 different single-file techniques (Reciproc-Blue®, WaveOne-Gold® and XP-EndoShaper®), with a new method using CBCT and 3D reconstruction. Methods In this prospective study, thirty human lower premolars from healthy patients were used, in which extraction was indicated for orthodontic reasons. All the teeth used were caries- and restoration-free with complete root development, without signs of periodontal disease or traumatic occlusion, and with only one straight canal (up to 25º curvature). Teeth were randomly divided into three different groups: Reciproc-Blue, WaveOne-Gold and XP-EndoShaper. CBCT scans before root canal preparation were used to create a 3D reconstruction with RHINOCEROS 5.0 software to assess the initial canal volume, and then compared with 3D reconstructions after canal preparation to measure the increase in canal volume. Student's t test for paired data were used to determine statistically significant differences between the before and after canal volumes. Anova test was used to determine statistically significant differences in the percentage of canal volume increase between the groups and Tukey's post-hoc test were used to paired comparison. Results Reciproc-Blue showed the higher increase in canal volume, followed by WaveOne-Gold and XP-EndoShaper (p = 0.003). XP-EndoShaper did not show a statistically significant increase in canal volume after root canal preparation (p = 0.06). Conclusion With this model, Reciproc-Blue showed higher increase in root canal volume, followed by WaveOne-Gold, while XP-EndoShaper did not significantly increase root canal volume during preparation.